Review of the literature on merger waves - Sangjun Cho; Chune Young Chung (Journal of Risk and Financial Management, 2022)
Over the past few decades, the rapid growth of mergers and acquisitions (M&As) has received interest from academics and practitioners. While M&As continue to be the subject of thorough investigation from a corporate governance standpoint, comparatively less effort has been made to organize and link empirical findings with neoclassical economic theories. Herein, we explore monumental studies from several strands of M&A literature, emphasizing the motives and outcomes of horizontal M&As in the US market.
Keywords: G30; G32; G34; 650; M&A; takeovers; firm performance; merger waves; sharing economy; cross-border acquisitions; innovations; R&D; post-merger performance; agency conflict; anti-takeover provisions